MERDEKA BELAJAR DALAM KONTEKS PENDIDIKAN KEWARGANEGARAAN : SUATU ALTERNATIF PEMBINAAN SISWA MENJADI WARGANEGARA YANG SADAR HAK DAN KEWAJIBANNYA - Kusnadi (Prosiding Temu Ilmiah Nasional Guru, 2023)
This article aims to discuss how civic education has an important role in forming citizens who are aware of their rights and obligations in a democratic country. However, the conventional approach in delivering civics curriculum material is often less attractive to students and unable to provide sufficient space for them to develop their full potential. Therefore, Merdeka Learning is an attractive alternative for fostering students to become citizens who are aware of their rights and obligations. Independent Learning is an educational concept that gives freedom to students to manage their learning process, including determining the material they want to learn, the learning methods used, and assessing their learning progress. In the context of citizenship education, Merdeka Learning provides opportunities for students to choose topics that are relevant to the rights and obligations of citizens, such as human rights, political participation, social issues, and the history of the struggle for independence. The method used is a qualitative approach to the method of literature study. Literature study is the process of finding, analyzing, and analyzing sources of information that are relevant to a particular research topic or study. Through the Merdeka Learning approach in civics education, it is hoped that students can become more active, creative, and innovative in developing their understanding of rights and obligations as citizens. They will also learn to value differences, think critically, and participate actively in society. This research will further explore how Freedom Learning can be applied in the context of civics education and how it can influence the development of students to become citizens who are aware of their rights and obligations. It is hoped that the results of this research can contribute to the development of civics education that is more relevant and meaningful in facing the challenges of an increasingly complex global society.